Review of CHESS score in SAH patients in local Malaysian population - Sze-Voon, Yee (2018)
Background and Objective Chronic hydrocephalus caused by subarachnoid hemorrhage is a reversible and treatable condition. To date, existing clinical scores for predicting the development of posthemorrhagic hydrocephalus are few and difficult to apply in the clinical settings. Chronic Hydrocephalus Ensuing Subarachnoid Hemorrhage Score (CHESS) was first published in 2015. Although it showed promising results, no external validation has been done outside Europe. We designed this study to validate the accuracy and reliability of CHESS score and to also look for other factors that may cause post-hemorrhagic shunt dependent hydrocephalus. Methods A total of 130 patients with acute subarachnoid haemorrhage from 2 tertiary neurosurgery centres in Malaysia were analysed using the parameters in CHESS score. The CHESS score was applied retrospectively and the results were compared with the patients’ clinical data of development of shunt-dependent hydrocephalus. Results were analysed using binary logistic regression analysis and Goodness-of-Fit test to determine the predictive value and its distribution with the original data. Results Thirty one percent of the studied population developed shunt-dependent hydrocephalus (n=41). CHESS score showed a OR of 2.184 with p value of 0.000 and 2 other risk factors were found to be strongly related to development of shunt-dependent hydrocephalus i.e. early infarct in CT brain (OR 0.182 ; p value 0.004) and Fisher grade >3 (OR 1.986; p value of 0.047). However, the population distribution of CHESS score is not consistent with the data of the original author. Conclusion CHESS score is a reliable tool in early prediction of shunt-dependent hydrocephalus post subarachnoid haemorrhage in Malaysia.